2019
DOI: 10.1177/1403494819890783
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in sickness absence: Do managers evaluate men and women differently with regard to the appropriateness of sickness absence?

Abstract: Aims: Women have much higher rates of sickness absence than men, but the causes of the difference are not well understood. This study examines whether managers have more lenient attitudes towards women’s than towards men’s absence, as this might contribute to higher rates of sickness absence among women. Differences between managers and other employees are also assessed. Methods: Vignettes were used to measure attitudes towards the legitimacy of sickness absence. The vignettes consisted of brief case descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Participants were concerned about absenteeism in the company, but there were mixed views of how this concern was influenced by gender. Our study findings show that males perceived females having higher absenteeism due to family responsibilities and childcare, which is similar to earlier studies comparing reasons for absenteeism by gender [ 33 , 34 ]. A study in India on absenteeism in pharmaceutical industrial workers revealed that 30% of sick leave was due to social responsibilities and family health concerns [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Participants were concerned about absenteeism in the company, but there were mixed views of how this concern was influenced by gender. Our study findings show that males perceived females having higher absenteeism due to family responsibilities and childcare, which is similar to earlier studies comparing reasons for absenteeism by gender [ 33 , 34 ]. A study in India on absenteeism in pharmaceutical industrial workers revealed that 30% of sick leave was due to social responsibilities and family health concerns [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…A review of population-based studies on gender differences in public beliefs and attitudes towards mental disorders found no clear pattern regarding the gender of the affected person [ 41 ]. Mastekaasa et al [ 21 ] did not find that vignette gender was associated with how Norwegian managers evaluated the appropriateness of sickness absence, irrespective of diagnosis. On the other hand, a report from the Swedish National Audit Office found that women with mild to moderate depression were sick listed 30% more than men despite similar functional limitations and decreased capacity to work [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, women more often than men indicated a mental condition to the male vignettes, and the likelihood of recommending care-seeking was higher among women. A Norwegian study, however, found no differences between women and men in attitudes to sick leave depending on gender of the written vignettes [ 21 ]. The study included a large variety of occupations and health conditions divided into male and female vignettes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies additionally show that human values are related to health outcomes and health behavior (Beller, 2021;Nordfjaern & Brunborg, 2015). Work factors are also shown to be associated with sick leave patterns (Laaksonen et al, 2010;Markussen et al, 2011) and differences in attitudes toward sickness absence (Mastekaasa, Dale-Olsen, Hellevik, Løset & Østbakken, 2021), while some studies suggest that family composition is related to sick leave (Allebeck & Mastekaasa, 2004;Markussen et al, 2011;Mastekaasa, 2013). Human value priorities are further theorized to orient choices and investments in central life domains such as work and family (Schwartz, 2003), and they have been found to be associated with, for example, the likelihood of being self-employed (Morales, Holtschlag, Masuda & Marquina, 2019) and attitudes toward voluntary childlessness (Merz & Liefbroer, 2012).…”
Section: Potential Confounders Of the Association Between Human Value...mentioning
confidence: 99%